(3TQM GdbjGS aj GdefWbs - (3eMeO Hf eUWai GdCQVQheis; (3ehSi GdHgdhGfjs
(3ChdgG (B:s
(3hHYO , ajbhd GdYHO GdabjQ Edi QHg GdZfi eMeO Hf eUWai GdCQV Qhei s
(3BNQgG (B:s
(3gPG dG jNai Ydi GdeJJHY GdeJCed GdKGbH hEf Nai Ydi GdeMLhH GdHdjO s
(3HgG fXGe GdJYbjHIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3efWb Mdje (B9) s
Keywords: (3GdadSaI hGdefWbs